The Illustrated Dioskourides Codices and the Transmission of Images during Antiquity. (November 2019) - Thomas, Joshua J.
Abstract: A parchment codex of the early sixth century a.d ., now in Vienna, contains a remarkable series of nearly 400 full-page illustrations of individual botanical species. These illustrations accompany an alphabetical recension of a pharmacological treatise on the medicinal properties of plants written by Dioskourides of Anazarbos, a Greek author of the first century a.d . Both the date of the codex and the style of its botanical illustrations have encouraged suggestions that the latter were modelled somehow on classical archetypes. This article presents new observations in support of the classical archetypes theory, but questions the traditional view that these archetypes were transmitted by 'illustrated texts' or 'pattern books' executed in papyrus or parchment. What follows is a new hypothesis concerning the nature of the artistic intermediaries used by painters, mosaicists and sculptors during antiquity.